Model Financial Technology (Fintech) Syariah di Sumatera Utara - Siti Mujiatun; Hanifa Jasin; Muhammad Fahmi; Jufrizen Jufrizen (Politeknik Ganesha Medan, 2022)
This study aims to analyze Islamic Financial Technology (Fintech) using a SWOT analysis approach in North Sumatra. This type of research uses qualitative research methods. Data collection techniques in research using interviews. This research was conducted in several Islamic Banks in North Sumatra, such as Bank Syariah Indonesia, BCA Syariah, Bank Mega Syariah, Bank Niaga Syariah and Bank Muamalat Indonesia. Data analysis technique with SWOT analysis. The results show that the opportunity for Islamic financial technology for Islamic banking is how financial technology as a newcomer can synergize with financial institutions, especially Islamic banking. After the researchers conducted the analysis, the conclusion of the financial technology opportunity is the opportunity to create income for Islamic Banking through collaboration with financial technology companies. And can facilitate customers such as transfer of funds, payments, borrowing capital, credit to asset management. Furthermore, the challenge for Islamic banking because of the existence of financial technology is the rise of crime in the world of technology and information.